Logistics Management of the CG Group Distribution Center: Improving Logistics Management Factors and Service Quality at the CG Group Distribution Center (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purposes of this study were to determine logistics management factors, the quality of services level, and relationship between Logistics management and the quality of the services level of Central department stores. A questionnaire was distributed to 330 customers who used services at distribution center of Central department stores and analyzed data in statistic application of percentage, mean, standard deviation, t-test, f-test, one-way Anova, Pearson correlation, and multiple regression analysis.The results of the study showed that most of respondents were male, aged 21-30 years old, were single, graduated lower than vocational level, staff level position, and had 2-5 years job experienced with company. The overall picture of the opinions on Logistics management, such as receipt products, storage, distribution, services, transportation, and returned merchandises were at a high level. The different personal behavior patterns, such as positions, job lengths affected the quality of the services with a statistically significant .05 level. Factors of Logistics management in the field of receipt products, storage, distribution, transportation, and returning products had a very high level of relationship in the same direction. Logistics management factors had an influence on the quality of products distribution services in the products condition, such as company employees dress modestly according to the regulation, delivery of the right products, correct location, on time delivery, competent employee along with solving problems, there are facilities that are ready and sufficient for services which influencing the quality of services at Central department stores, Bang Na district distribution center with a statistically significant .05 level.Suggestions from the study results were that administrative officers should emphasize on allocation of investment funds to purchase tools and equipment for receiving products to meet the customers requirement, to enhance the image of the organization, to be accepted by customers, to improve the quality of receipt good in term of storage, and should pay attention to distribution process. In addition, focus on the development of various information systems in order to increase communication channels for the return of products which need to be convenient, quick, and more comfortable for customers.